How dispositional optimism–pessimism relates to early adolescents’ emotional maladjustment during COVID-19? Moderating roles of knowledge about the disease and parent-child conflicts - Jiang, Yongqiang; Wu, Dazhou; Lin, Xiuyun (Frontiers in Psychiatry, 2025)
IntroductionThe COVID-19 pandemic and associated containment measures changed the daily lives of children and adolescents around the world. To investigate the individual differences in emotional maladjustment under the COVID-19 pandemic, this study focused on the roles of dispositional optimism-pessimism, knowledge about the COVID-19 disease, and conflicts with parents among Chinese early adolescents.Methodedge about the COVID-19 disease, and conflicts with parents among Chinese early adolescents. The participants were 2,958 early adolescents aged 10 to 14 years old who completed online questionnaires during the pandemic.ResultsWhile higher pessimism and lower optimism both led to increased emotional maladjustment, pessimism made a greater contribution. Knowledge about the disease and parent-child conflicts were both risk factors for adolescents’ emotional maladjustment, yet optimism and pessimism interacted with different factors. More knowledge about the disease intensified the effect of pessimism, and more parent-conflict undermined the effect of optimism.DiscussionOur findings provide directions for future aid in adolescence during hard periods depending on one’s personality.